Aplikasi Pembelajaran Berbasis E-learning Pada Pelajaran Agama Islam SMP IT Nur Hidayah Surakarta Menggunakan Metode UML - Abdurrozak, Miftah; , Aris Rakhmadi, S.T., M. Eng (2016)
Teaching and learning in education have a variety of learning methodsto support the process of delivering subjects from teachers to students. As advances in information technology,Internet-based learning method becomes alterative learning tool to give subjects outside the classroom and share articles lessons taught in the classroom.The purpose of this research to designlearning applications based e-learning on the Islamic religious lessons. Web-based E-learning is designed to assist teachers in implementing alternative learning methods for students in the study subjects given by the teacher outside the classroom. This research use UML to design e-learning, which consist use-case diagrams and activity diagram. E-learning is designed using the programming language PHP and MYSQL database. Obtained cost material from the teacher related data on existing subjects. Results obtained in the form of e-learning program based web to support teachers and students in the process of teaching and learning or quiz exercises that can be done outside the classroom.